The Feasibility of Gamma Irradiation for Developing Malaria Vaccine - M. Syaifudin; D. Tetriana; Darlina Darlina; S. Nurhayati (PPIKSN-BATAN, 2011)
Malaria, a plasmodial disease, causes more than one million deaths per year and has a significant public health impact. Improved access to prompt treatment with effective antimalarial drugs need to be conducted for prevention of infection in high risk groups. However, the parasite as causal agent has exhibited a potential danger of wide-spread resistances. This warning has directed attention to the study of alternative methods of protection against the disease, among them is to do the immunization. A deeper understanding of the nature and regulation of protective immune mechanisms against this parasite will facilitate the development of much needed vaccines. Developing a malaria vaccine remains an enormous scientific, technical, and financial challenge. Currently a vaccine is not fully available. Among the practical applications of radiobiological techniques that may be of considerable interest for public health is the use of ionizing radiation in the preparation of vaccines. Convincing data were reported that sporozoites of Plasmodium berghei irradiated with X- or gamma-rays, provide an antigenic stimulus effective to induce a protective immune response in mice and rats against subsequent sporozoite infection. Irradiated parasites are better immunogens than killed ones and although non-infective they are still metabolically active, as shown by continued protein and nucleic acid synthesis. There is a substantial number of data from human studies demonstrating that sporozoites attenuated by radiation are potent inducers of protective immunity and that they are safe and do not give rise to the asexual erythrocytic infections that cause malaria. This vaccine is relatively inexpensive to produce, easy to store, and transportable without refrigeration. A long-term effort and commitment to providing resources must be maintained and increased to achieve the goal of a malaria vaccine candidate where ionizing radiation as a tool to prepare is seemingly feasible. Received: 20 November 2010; Revised: 11 July 2011; Accepted: 01 August 2011